Complex of anti-crisis measures for enterprise trading in pet care products - Usov, Denys; Усов, Денис (Запоріжжя: ТДАТУ, 2026)
Modern economic conditions demand that businesses remain flexible and proactive, developing strategies before turbulence arises. An enterprise specialising in pet care products operates in a resilient niche, yet macroeconomic instability and declining disposable income can still cause stagnation. A comprehensive anti-crisis plan, grounded in competitive analysis, demand structure, consumer behaviour, and product specifics, is essential for sustaining profitability and strengthening market position.
Keywords: anti-crisis measures; pet care products